Genome-wide association study and transcriptome analysis reveal key genes controlling fruit branch angle in cotton - Shao, Panxia; Peng, Yabin; Wu, Yuanlong; Wang, Jing; Pan, Zhenyuan; Yang, Yang; Aini, Nurimanguli; Guo, Chunping; Shui, Guangling; Chao, Lei; Tian, Xiaomin; An, Qiushuang; et al. (Frontiers in Plant Science, 2022)
Fruit branch angle (FBA), a pivotal component of cotton plant architecture, is vital for field and mechanical harvesting. However, the molecular mechanism of fruit branch angle formation is poorly understood in cotton. To uncover the genetic basis for FBA formation in cotton, we performed a genome-wide association study (GWAS) of 163 cotton accessions with re-sequencing data. A total of 55 SNPs and 18 candidate genes were significantly associated with FBA trait. By combining GWAS and transcriptome analysis, four genes underlying FBA were identified. An FBA-associated candidate gene Ghi_A09G08736, which is homologous to SAUR46 in Arabidopsis thaliana, was detected in our study. In addition, transcriptomic evidence was provided to show that gravity and light were implicated in the FBA formation. This study provides new insights into the genetic architecture of FBA that informs architecture breeding in cotton.